"You cannot be serious". The translation of sport science research to the tennis court - Fernández-Fernández, J.; Santos-Rosa, F. J. (European Journal of Human Movement, 2023)
Tennis has become a major sport in the last few years, with players such as Novak Djokovic, Serena Williams, Roger Federer, Iga Swiatek, Rafael Nadal or Carlos Alcaraz, generated a lot of public interest. Behind the curtains, practitioners (i.e, tennis coaches, strength and conditioning coaches, physiotherapists) have to invest a lot of time and hard work to improve the quality of the game (1), which is supposed to be supported by scientific research. Unfortunately, as in any other sport, tennis training is sometimes based on old beliefs and anecdotal evidence from coaches, lacking scientific support. In this regard, it ´s not unusual to hear from tennis coaches things like: "research is for universities, not for tennis", "this is too complicated" or "these a re not people from tennis", when sport - scientists try to apply relevant up - to - date research findings to develop or optimize practice. This step, defined as "evidence - based practice", and described as the integration of coaching expertise, athlete values, a nd the best relevant research evidence into the decision - making process for day - to - day service delivery to athletes (2), is often neglected in the "tennis - world". [...]